2022
DOI: 10.1039/d1fo03223b
|View full text |Cite
|
Sign up to set email alerts
|

Development of the digestive system in early infancy and nutritional management of digestive problems in breastfed and formula-fed infants

Abstract: Food digestion and absorption in infants are closely related to early growth and long-term health. Human milk and infant formula are the main food sources for 0-6 month-old infants. Due...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 103 publications
1
5
0
1
Order By: Relevance
“…5 Recently, increasing clinical evidence has shown that infant formulas supplemented with sn-2 palmitic TAGs have beneficial influences on infants, including fat digestion and absorption, calcium absorption, bone matrix quality, consistency of stools, sleeping time and intestinal microflora. 6,7 Similar results have also been observed by feeding rats or mice with sn-2 palmitic TAGs. 8,9 Besides, our recent research reported that dietary sn-2 palmitic TAGs might increase lipid metabolic activity for energy supply in Sprague-Dawley rats as measured by histopathology and molecular biology techniques.…”
Section: Introductionsupporting
confidence: 74%
“…5 Recently, increasing clinical evidence has shown that infant formulas supplemented with sn-2 palmitic TAGs have beneficial influences on infants, including fat digestion and absorption, calcium absorption, bone matrix quality, consistency of stools, sleeping time and intestinal microflora. 6,7 Similar results have also been observed by feeding rats or mice with sn-2 palmitic TAGs. 8,9 Besides, our recent research reported that dietary sn-2 palmitic TAGs might increase lipid metabolic activity for energy supply in Sprague-Dawley rats as measured by histopathology and molecular biology techniques.…”
Section: Introductionsupporting
confidence: 74%
“…The component differences of baby formulas from mother's milk increase the possibility of mild digestion problems in babies fed with formula. Moreover, mothers who give formula or supplementary food to their babies experience problems with breastfeeding (Tanrıkulu et al, 2012;Jiang et al, 2022). Thus, it is not recommended to feed babies with formula or any other supplementary food (Yılmaz, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…[84][85][86] The acid in the gastric lumen activates pepsinogen, an inactive precursor released by the gastric mucosa cells. [87][88] There is a correlation between stomach mucosal damage caused by HP-LPS and the activation of pepsinogen and the production of histamine. [7,89] A. marmelos has shown an antisecretory effect by attenuating acidity and pepsin activity, among other acid secretory measures.…”
Section: Chemistryselectmentioning
confidence: 99%
“…In reality, the presence of pepsin, which is abundant in the gastric lumen, is necessary for the development of stomach ulcers; otherwise, gastric acid does not cause ulceration [84–86] . The acid in the gastric lumen activates pepsinogen, an inactive precursor released by the gastric mucosa cells [87–88] . There is a correlation between stomach mucosal damage caused by HP‐LPS and the activation of pepsinogen and the production of histamine [7,89] .…”
Section: Gastro‐protective Activities Of a Marmaelosmentioning
confidence: 99%